Dielectrical and electrical properties of PVA-NaI composites - Najeeb, Hussein Neama (Iraqi Journal of Physics, 2019)
The electrical characteristics of polyvinyl alcohol PVA doped with different concentrations (0, 1, 2, 3 and 4wt%) of sodium  iodide NaI powder were studied. The films are prepared using solution casting technique, in order to investigate the effect of sodium iodide NaI additions on the electrical properties of PVA host. The D.C conductivity measured by measuring the D.C electrical resistance using the Keithly Electrometer type 616C, and for different temperatures ranging from 30 – 70oC.          The dielectric properties measured by measuring the capacitor and the loss angle tangent as a function of the alternating electric field frequency using the Agilent impedance analyzer 4294A, within the frequency range 50 – 6 ×106 Hz at room temperature.  The experimental results showed that the dielectric constant is decrease with increase frequency of applied electrical field and increase with increasing concentrations, dielectric loss is increase with increasing frequency of applied electrical field to be 1MHz after this it was decreasing, A.C electrical conductivity are increasing with increasing frequency of applied electrical field, also, the results showed that the D.C electrical conductivity are increasing with increase concentration of NaI and temperature, activation energy are decreasing with increase concentration of additive salt.